Implementation of the Living Qur'an Concept in Starting Learning in MA Matholi'ul Huda Bugel - Muhammad Abid Robi'un Nuha; Azzah Nor Laila (EDUCAN : JURNAL PENDIDIKAN ISLAM, 2025)
The Qur'an is a verse of Allah which literally means "perfect reading. The implementation of the concept of Living Qur'an in learning at MA Matholi'ul Huda Bugel is an important focus in the study of Islamic education This research underlines the importance of teachers' creativity in delivering material, which can be adapted in the implementation of learning at MA Matholi'ul Huda Bugel to improve students' ability to read the Qur'an. "Teaching Material Development Practical Guidelines For Reading Al-Qur'an in Learning Al-Qur'an at Griya Al-Qur'an of Surabaya" by Khoirul Huda and Mahsun Jayadi.  highlights the challenges in the development of teaching materials effective. The education taught is an education that is considered to be able to provide the best provisions for students. There are many ways done by educational institutions to improve the quality of students' morals. The methodology of this study uses a qualitative approach to gain a deep understanding of the implementation of the concept of Living Qur'an in learning at MA Matholi'ul Huda Bugel.